Lucky the Leprechaun and the rainbow dragon - Wurfel, Marlene (My University, 2016)
Happy St. Paddy's day. In this original Tales from the Lilypad story by Marlene Wurfel, Lucky the Leprechaun finds more than he was expecting in a pot of gold. This one has gold, mischief, rainbows, magic, dragons, fairies, shamrocks and a good mug o' dandelion ale.
Keywords: storytelling; children's stories